In Pursuit of Legitimacy: The Muslim Brotherhood’s Discourse on Democracy and Human Rights in Post-2013 Egypt - Bosmat Yefet (Religions)
This article examines the Muslim Brotherhood’s strategic framing of democracy and human rights in Egypt following the 2013 military coup, contributing to scholarship on the movement’s adaptation to repression and political exclusion. Employing framing analysis, this study analyzes official statements from Ikhwanonline from 2015 to 2024, when the old guard regained control over the organization’s messaging, in order to explore how the movement operated to reclaim political legitimacy amid repression, exile, and internal fragmentation. The findings indicate that despite the failure of its strategic commitment to democracy as a pathway to political dominance—culminating in its ousting—the old guard continues to espouse this framework. The movement frames its predicament and struggle as part of the Egyptian people’s broader fight against oppression and authoritarianism. This rhetorical continuity persists despite internal divisions and reformist calls for a more proactive approach, highlighting the movement’s reliance on established discursive strategies not only to confront regime repression but also to avoid engaging with questions of institutional reform.